PENDAMPINGAN KEGIATAN MENGAJI UNTUK MENAMBAH WAWASAN ISLAM DAN MEMPERLANCAR BACAAN AL-QURAN UNTUK ANAK-ANAK DESA GARUNG KECAMATAN JEBIREN RAYA - M Riffaii; Nurul Wahdah; Nur Inayah Syar; Muhammad Syabrina (LP3K Lampung, 2023)
The Community service is carried out through real work lecture activities, in the community in improving the spirituality of children and providing assistance in learning the Quran in order to facilitate the reading of the Quran. This activity was carried out as a form of effort to improve religion which was blocked a lot during PPKM during the Covid-19 period. The impact of covid 19 on children's spirituality has an impact on the lack of knowledge of Islam in children, many children have experienced delays in reading the Quran due to limited places to learn the Quran and many children are starting to forget how to read the Quran because they do not learn to recite any more. This devotion uses sociological and religious approaches. Implemented for an approach to society and children and people who are Muslims. From the results of the service, it can be seen that before the mentoring was held, there were still many children who still lacked knowledge of the Islamic religion and there were still many who could not read the Quran. However, after the service, there began to be many children who had knowledge about agama Islam, and there began to be children who could read the Quran fluently which could be used for provisions in the future.